1098. Clinical Features and Outcomes of United States Marine Corps Recruits Hospitalized With Shiga Toxin-Producing Escherichia coli Infection and Hemolytic–Uremic Syndrome. (26th November 2018) - Sanders, Terrel; Ellis, Graham; Castrovinci, Philip; Deiss, Robert; Maves, Ryan
Abstract: Background: Shiga toxin-producing Escherichia coli (STEC) is associated with potentially life-threatening dysentery, along with its most feared complication, the hemolytic–uremic syndrome (HUS), occurring in up to 20% of STEC-infected patients. 10–30% of patients may experience chronic renovascular and neurologic sequelae after acute resolution. We describe clinical features and outcomes of a young, male military recruit population hospitalized for STEC infection and HUS in 2017. Methods: Between October and November 2017, an STEC outbreak occurred at Marine Corps Recruit Depot San Diego (MCRD-SD) affecting 244 recruits, including 30 who required hospitalization. Polymerase chain reaction and pulsed-field gel electrophoresis of stool culture isolates demonstrated stx2 -positive E. coli O157:H7. Thirty recruits required hospitalization; the remaining 214 underwent daily clinical evaluation and laboratory testing at MCRD with daily crystalloid volume expansion until the resolution of dysentery. Results: 50% (15/30) of hospitalized recruits developed HUS and were initially managed with volume expansion until the onset of oliguria. Five recruits with severe HUS required hemodialysis; six required intensive critical care unit (ICU) admission; and three suffered from respiratory failure requiring mechanical ventilation. Average length of hospitalization was 10 days. Patients requiring hemodialysis received an average 7.4 days of renal replacement. Three patients experienced encephalopathy with seizures and were managed with levetiracetam and corticosteroids for Stx-induced cerebral edema. One patient received eculizumab, a terminal complement inhibitor approved for atypical HUS, with resolution of seizures and return to his neurocognitive baseline but with persistent electroencephalographic abnormalities. There were no deaths, and all recruits had recovery of renal function. Conclusion: This case series represents the largest STEC-HUS outbreak affecting a military population. Rates of HUS and mortality were lower than seen in prior outbreaks, in part due to a high level of baseline health and early detection and management of suspect cases. Early volume expansion and close monitoring of cases may have reduced the risk for HUS progression and long-term renal sequelae. Disclosures: All authors: No reported disclosures.